Exploring Cambodian Teachers' Views on Transformational Leadership of School Directors - Sereyrath Em; Sarom Mok; Rany Sam (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the Study: To explore Cambodian teachers’ perceptions of their school directors’ transformational leadership and analyze variations based on gender, age, educational background, and provincial location. Methodology: The study employed ANOVA for statistical analysis, using surveys with 20 statements to assess five aspects of transformational leadership. Data collection involved 639 participants across four provinces. Main Findings: No gender differences were observed. Significant differences existed by age, education, and province. Younger teachers (20–30 years) showed more positive attitudes and educational attainment influenced leadership perception. Novelty/Originality of this Study: This study highlights how age, education, and location shape teachers’ views on directors’ transformational leadership, emphasizing the need for adaptive leadership approaches to address diverse teacher expectations in Cambodia​ , where this type of study has not been done so far.